Complex Interplay between Absorber Composition and Alkali Doping in High‐Efficiency Kesterite Solar Cells. Issue 4 (4th October 2017) - Haass, Stefan G.; Andres, Christian; Figi, Renato; Schreiner, Claudia; Bürki, Melanie; Romanyuk, Yaroslav E.; Tiwari, Ayodhya N.
Abstract: Sodium treatment of kesterite layers is a widely used and efficient method to boost solar cell efficiency. However, first experiments employing other alkali elements cause confusion as reported results contradict each other. In this comprehensive investigation, the effects of absorber composition, alkali element, and concentration on optoelectronic properties and device performance are investigated. Experimental results show that in the row Li–Na–K–Rb–Cs the nominal Sn content should be reduced by more than 20% (relative) to achieve the highest conversion efficiency. The alkali concentration resulting in highest device efficiencies is lower by an order of magnitude for the heavy alkali elements (Rb, Cs) compared to the lighter ones (Li, Na, K). Utilization of a wide range of characterization techniques helps to unveil the complex interplay between absorber composition and alkali doping. A ranking of alkali for best device performances, when employing alkali treatment, resulted in the order of Li > Na > K > Rb > Cs based on the statistics of more than 700 individual cells. Finally, a champion device with 11.5% efficiency (12.3% active area) is achieved using a high Li concentration with an optimized Sn content. Abstract : Treatment with different alkali elements necessitates tuning absorber composition and specifically Sn content for achieving maximum performance of kesterite thin film solar cells. A ranking of alkali for best device performances is in the order of Li > Na > K > Rb > Cs, whereby an efficiency of 11.5% (total cell area) is achieved for a Li‐doped champion device.